Effect of PRID administration post-insemination on the establishment of pregnancy of dairy cows under commercial farm conditions - Brozos, C.; Tsousis, G.; Kiossis, E.; Tsakmakidis, I.; Karagiannis, I.; Boscos, C. (Journal of the Hellenic Veterinary Medical Society, 2019)
The aim of this study was to test the efficiency of progesterone supplementation post insemination (p.i.) in the fertility of dairy cows under commercial farm conditions. At initiation of the study, 405 cows from three farms -irrespective of their open days- were bred after showing heat or after synchronization. Subsequently, the cows were randomly allocated to receive a progesterone-releasing intra-vaginal device (PRID®) between D5 and D17 p.i (P4+, n=213), or to remain untreated (P4-, n=192). Pregnancy per artificial insemination (P/AI) did not differ between P4+ (42.3%) and P4- (41.2%, P = 0.82) groups. However, the treatment improved P/AI in cows enrolled in the study after the second p.p. insemination (46.8 vs. 25.5, P = 0.02). In the farm that showed the lower days to insemination before treatment, progesterone supplementation tended to raise the P/AI (48.2 vs. 23.5, P = 0.08). However, in the farm with the greater fertility the P4+ group had significantly lower P/AI than the P4- group (37.7 vs. 57.4, P = 0.03). Conclusively, the beneficial effect of the post-insemination administration of PRID is mainly apparent only after the second p.p. insemination and probably during early lactation when fertility is suppressed.